Geographies of knowledge creation in forest rights claims-making processes among Indigenous communities in Central India - Loivaranta Tikli (ELSEVIER SCI LTD, 2025)
This qualitative study explores the geographies of knowledge creation in forest rights claims-making processes in three Indigenous communities in Madhya Pradesh, India. In two of the villages, the process is described from the point where the Forest Rights Act is introduced to communities, to the lodging of claims and beyond. One of the villages had not been able to secure their community forest rights. The challenges to knowledge creation, and success factors to overcome the challenges, are explored through the analytical lens of space and the dynamics of distances in material and cognitive space. The main challenges include difficulties in understanding the legal language of the Forest Rights Act, difficulties in bridging the cognitive distance to the forest bureaucracy, and the geographical distance to the town where the offices are. The co-presence of a non-governmental organisation was necessary in bridging the geographical and cognitive distance. During the process, the residents developed a shared understanding of the concept of Community Forest Rights. The notion that the residents are the most skilled in protecting the forests where they live is one of the most commonly shared conceptual anchors to this understanding. In terms of tenure security, the development of shared understanding of forest rights helps in maintaining the perceptions of secure tenure and acts as a protective shield against violations to the forest rights in the future.